Prediction of Evaporation Changes in Half Well Reservoirs of Sistan By Using Randomized Simulator Models - Abbas Ali Ghaderi; heidar ali yosefian nazer (جغرافیا و توسعه, 2020)
Evaporation is one of the most important components of the hydrological cycle and its precise estimation is essential for many studies, including planning and managing water resources. In addition, water resource management has been considered on the basis of sustainable development in the world and sustainable development, in simple terms, is such a development and management that can clearly establish, maintain and enhance human quality of life at all times. Therefore, management of this vital resource in the context of the above definition is of more importance in countries with a dry and semi-arid climate. In this regard, evaporation is one of the climatic parameters and has affected the arid and semi-arid regions more than ever. Therefore, increasing awareness about the evolution of evapotranspiration is of great help to experts in the field of water resources management in the area of watershed management and agricultural operations.In Sistan, the high temperatures and winds have caused the total of 1.5 billion cubic meters of water stored in four half wells in Sistan to evaporate very large volume water annually from the surface of the half wells. Therefore, the purpose of this study is to calculate the evaporation rate, study the process of evapotranspiration,evaluate the accuracy of time series models including ARIMA,Holt-Winters, and extracting the trend models in estimating the evaporation rate and prediction of evaporation over the coming years in the Sistan partial water half wells.